1984
DOI: 10.1111/j.1559-1816.1984.tb02217.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effects of Monetary Incentives and Foot‐in‐the‐Door Strategies in Promoting Residential Electricity Conservation

Abstract: The relative effectiveness of incentive and minimal justification techniques in promoting electrical energy conservation among 90 homeowners was investigated. Subjects in the Questionnaire condition were asked to complete a short energy conservation survey. Those in the Commitment condition were asked to curtail their consumption of electricity by 15%. In the Questionnaire + Commitment condition, subjects received both requests. These three groups were compared to an Incentive condition, where individuals were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(49 citation statements)
references
References 28 publications
1
47
0
1
Order By: Relevance
“…These have covered a vast range of both antecedents and consequences of pro-environmental behavior. For instance, Katzev and Johnson (1983) and Pallak and Cummings (1976) demonstrated that commitment had longterm effects for reducing household energy use, however, later research did not find any support for long-term effects (Katzev & Johnson, 1984). Research on goal setting (Becker, 1978;McCalley & Midden, 2002) has shown that goal setting combined with feedback led to significant reductions in energy use.…”
Section: Current Understanding Of Proenvironmental Interventionsmentioning
confidence: 99%
“…These have covered a vast range of both antecedents and consequences of pro-environmental behavior. For instance, Katzev and Johnson (1983) and Pallak and Cummings (1976) demonstrated that commitment had longterm effects for reducing household energy use, however, later research did not find any support for long-term effects (Katzev & Johnson, 1984). Research on goal setting (Becker, 1978;McCalley & Midden, 2002) has shown that goal setting combined with feedback led to significant reductions in energy use.…”
Section: Current Understanding Of Proenvironmental Interventionsmentioning
confidence: 99%
“…Such strategies send non-price signals to participants that activate intrinsic and extrinsic motivation. Besides comparative feedback, motivational strategies also include the use of competitions (e.g., McMakin et al, 2002) and goal-setting (e.g., Katzev and Johnson, 1984) where participants are assigned or select non-binding goals over a defined period of time.…”
Section: The Power Of Normsmentioning
confidence: 99%
“…Pricing information has been widely used to induce individuals to save energy (Battalio et al, 1979;Katzev and Johnson, 1984;. Despite the direct financial benefits of saving energy, research indicates that providing information about the cost of energy use does not necessarily affect energy use behavior among households (Lindén et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The use of norms on collective behavior has strong effects, such as Peterson et al's (2007) findings on energy consumption in dormitories. The use of feedback and/or norms on household bills is now a strong and repeated finding for energy (see Hayes and Cone 1977); (Winett et al 1982); (Midden et al 1983); (Katzev and Johnson, 1984); (Brandon and Lewis 1999); (Matsukawa 2004 In a slight variation on the use of social norms, public shaming and stigmatisation has been explored in relation to tax compliance. This is not the case with energy, likely linked to the fact that energy is a non-compulsory area and it is harder to tap into social norms against which people can be stigmatised or shamed.…”
Section: Social Normsmentioning
confidence: 99%
“…Both Kirchler et al (2007) and the Behavioural Insights Team (BIT) (Cabinet Office 2012) have reviewed the evidence on the impact of emphasising positive social norms (i.e. highlighting good behaviour from reference groups) on tax compliance, and shown that it is also an effective way of increasing tax compliance in individuals.…”
Section: Social Normsmentioning
confidence: 99%